MXene-integrated smart textiles and their applications - Narinen, Aaron (My University, 2025)
The amount of wearable electronics and portable energy storage is continually increasing. Consequently, interest in MXene-integrated smart textiles and their applications is rising rapidly, though it has yet to be fully mastered. Numerous challenges remain to be addressed before the technology is ready for large-scale production. This thesis reviews the various synthesis methods for MXenes, fabrication approaches for integrating MXenes into smart textiles, and the applications that MXene-integrated smart textiles can have. There are two main approaches for synthesising MXenes. The most commonly used top-down method involves etching precursor materials known as MAX phases to synthesise MXenes. The other approach is the bottom-up method, in which MXene is synthesised by directly growing them from precursor materials in the gaseous or vapour phase. The scalability of the synthesis process presents one of the limiting issues for large-scale production due to the usage of harsh chemicals, high energy consumption, lack of precision, long synthesis times, and low production yields. However, several methods, such as low-temperature molten salt etching (LTMS), have demonstrated significant potential for large-scale production. Chemical vapour deposition (CVD) has also yielded promising results, as it can precisely control the size and symmetry of MXenes. Yet, further research is still necessary to achieve reliable and reproducible results in large quantities. CVD is the optimal choice when a precise structure of MXene is required for its application. The desired properties for specific applications involving MXene-integrated smart textiles can be fine-tuned at every step, from selecting the MXene synthesis method to utilising the fabrication approach, thereby further enhancing the desired properties such as conductivity. While the synthesis, fabrication approaches, and applications of MXenes in smart textiles have shown remarkable progress and results in all areas, further research is still required to tackle the challenges of durability, stability, environmental concerns, efficiency, and cost that limit the large-scale production of MXene-containing smart textiles. This thesis compares these methods regarding process conditions and product quality. We then examine various fabrication methods for MXene-integrated smart textiles and their extensive range of applications, including energy harvesting, transfer, storage, and use in various heating, sensing, and multifunctional applications. Complete multifunctional wearable smart garments that harvest energy from the human body, store it in a supercapacitor, and utilise it in applications such as joule heating or medical sensing can be produced entirely with MXene-integrated smart textiles. The applications for this type of garment continue to expand, and the properties of MXenes make them optimal for fields such as medical applications and outerwear.
Keywords: MXene, synthesis, smart textiles, 2D nanomaterials